The effects of hedge fund ownership on idiosyncratic risk - Gama, Vasco Mendes Pinto Teles da (2016)
This thesis studies the effect of the level of hedge fund ownership on the idiosyncratic volatility of firms. In particular we hypothesize that a high level of hedge fund ownership leads to an increase in the idiosyncratic volatility of highly idiosyncratic volatile while leading to a decrease in the idiosyncratic volatility of low idiosyncratic volatile stocks. This hypothesis is tested using panel-regression analysis. The analysis conducted provides evidence that supports the main research hypothesis. The hypothesis is further associated with stop loss constraints faced by the funds that prevent them from exercising their role of market stabilizers while studying how the 2008 crisis affected this cross-sectional trend.